Предмет: Математика,
автор: Nastasyaplaton12
5/6y-3/4y+1=2/3y-1/6
Ответы
Автор ответа:
0
5/6y - 3/4y + 1 = 2/3y - 1/6
5/6у-3/4у-2/3у=-1/6-1
-7/12у=-1 1/6
у=-7/6:(-7/12)
у=-7/6*(-12/7)
у=2
5/6у-3/4у-2/3у=-1/6-1
-7/12у=-1 1/6
у=-7/6:(-7/12)
у=-7/6*(-12/7)
у=2
Автор ответа:
0
ставь сердцу
Похожие вопросы
Предмет: Английский язык,
автор: fedor8526
Предмет: Математика,
автор: matveevoleg000p2nxot
Предмет: Алгебра,
автор: sunlee4ko
Предмет: Математика,
автор: gromoboyka01
Предмет: Информатика,
автор: behope65